Fluoride removal by palm shell waste based powdered activated carbon vs. functionalized carbon with magnesium silicate: Implications for their application in water treatment - Choong, Choe Earn; Wong, Kien Tiek; Jang, Seok Byum; Nah, In Wook; Choi, Jaeyoung; Ibrahim, Shaliza; Yoon, Yeomin; Jang, Min (Elsevier, 2020)
In this study, palm shell activated carbon powder (PSAC) and magnesium silicate (MgSiO3) modified PSAC (MPSAC) were thoroughly investigated for fluoride (F−) adsorption. F− adsorption isotherms showed that PSAC and MPSAC over-performed some other reported F− adsorbents with adsorption capacities of 116 mg g−1 and 150 mg g−1, respectively. Interestingly, the MgSiO3 impregnated layer changed the adsorption behavior of F− from monolayer to heterogeneous multilayer based on the Langmuir and Freundlich isotherm models verified by chi-square test (X2). Thermodynamic parameters indicated that the F− adsorption on PSAC and MPSAC was spontaneous and exothermic. PSAC and MPSAC were characterized using FESEM-EDX, XRD, FTIR and XPS to investigate the F− adsorption mechanism. Based on the regeneration tests using NaOH (0.01 M), PSAC exhibited poor regeneration (<20%) while MPSAC had steady adsorption efficiencies (∼70%) even after 5 regeneration cycles. This is due to highly polarized C–F bond was found on PSAC while Mg–F bond was distinguished on MPSAC, evidently denoting that the F− adsorption is mainly resulted from the exchange of hydroxyl (-OH) group. It was concluded that PSAC would be a potential adsorbent for in-situ F− groundwater remediation due to its capability to retain F− without leaching out in a wide range pH. MPSAC would be an alternative adsorbent for ex-situ F− water remediation because it can easily regenerate with NaOH solution. With the excellent F− adsorption properties, both PSAC and MPSAC offer as promising adsorbents for F− remediation in the aqueous phase. © 2019 Elsevier Ltd